METAMORPHOSES OF AUTHORITY: NOTES ON THE NOTION OF AUTHORITY IN TODAY'S CULTURE - Calmon Nabuco Lastoria, Luiz Antonio [UNESP]; Duci, Juliana Rossi [UNESP] (Univ Metodista Piracicaba-unimep, 2017)
This article aims to present the concept of transformations such as this authority figure in the Western tradition. Taken in its Latin etymological while constitutive element of Roman tradition, the discussion of the concept involves the transformations suffered under the impacts caused by modernity: concussions in the family, social and economic life. Such transformations reach the production of subjectivity today the extent to which they apply traditional substrates such as paternal figures and the teacher, and the text itself. This phenomenon tends to result in substantive changes in the understanding of authority in the field of education, in particular in that mode currently expands in the Brazilian scenario - distance education. The tours presented here uphold the social criticism psychoanalytically oriented and assume a possible shift of authority considered traditional toward the new audiovisual brackets marked by the use of information and communication technologies.
Keywords: AUTHORITY; CRITICAL THEORY OF SOCIETY; SUBJECTIVIT; INFORMATION AND COMMUNICATION TECHNOLOGIES